Diocesan authorities action taken in connection with the decree of the State Council of the People’s Republic of Poland of 31 December 1956 on the organization and staffing of Church, based on selected dioceses - STĘPIEŃ, MAREK (Prawo Kanoniczne, 2017)
After World War II, the Communists assumed power in Poland. Their actions were aimed at rapid implementation of the principles of Marxist philosophy through, among others, reducing and then preventing the functioning of the opposition. At the front of the ideological struggle stood also the Catholic Church, whose activity was considered by the state as a major obstacle in achieving the set goals. The pastoral activity of the Church in Poland was curbed considerably at that time, and in many cases was even impossible. At the beginning of 1957, the Decree of the State Council of 31 December 1956 on creating and staffing church positions came into force. This decree was less restrictive towards the clergy of the Catholic Church in Poland than the previous regulations in this matter. The activity of the state bodies focused on preventing the people who were considered hostile to the regime of the People’s Republic of Poland from being appointed to the positions of pastors and parish administrators. The Decree is the evidence of breaking the law by the state officials in order to impede the Church. The article describes the operation of the diocesan authorities taken in connection with the Decree of the State Council of the People’s Republic of Poland of 31 December 1956 on the organization and staffing of Church, based on selected dioceses.